(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The prime purpose of this analysis is to evaluate the value of response reduction factor of RC frames by considering various factors into account. As we are aware about that there is significant difference in the forces which are generated during earthquake than the structure is actually to be designed to withstand against these forces. We cannot design the structures for real values of seismic forces as it is uneconomical from various aspects. There is a necessity to reduce the actual severity of earthquake and to achieve this, rresponse reduction factor is used it is the factor by which the actual base shear force should be reduced, to obtain the design lateral force during design basic earthquake (DBE) shaking. The response reduction factor (R) is basically depends on Over strength (Rs), Ductility (Rµ), Redundancy (RR). There is no explanation given in (IS1893-2000) code for various values of response reduction factor used in, so it is difficult to proceed the execution of seismic design without firm basis. Also in terms of various factors such as ductility and over strength, IS code does not separate the component of response reduction factor (R) explicitly. Currently in present work attempt has been made to evaluate the actual value of response reduction factor for RC buildings with plan irregularity, variation in height of building and the effect of various seismic zones on response reduction factor. Also the comparison is made on the basis of importance factor, type of foundation soil and lateral load resisting system by non-linear static pushover analysis using SAP2000 and compare results with values given in IS code 1893(2000). The frames were designed as per specifications of IS 4562000.The lateral loads acting on the frames were taken from the specifications of IS 1893 2002 (Part1).